PENGARUH MARKET ORIENTATION DAN NETWORKING TERHADAP VOLUME PENJUALAN (Studi pada Tandjaja Farm Pare) - Eric Ardiansyah; Rafikhein Novia Ayuanti; Angga Permana Mahaputra (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to determine the effect of market orientation and networking on sales volume (Study on Tandjaj Farm Pare). The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to retailers at Tandjaja Farm Pare and calculated using the SPSS Version 25 application. The population in this study were all livestock retailers at Tandjaja Farm, totaling 400 people, and 80 samples were obtained from calculations using the Slovin formula. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-Test, F-Test, and R2 Determination Coefficient Test. In the validity test, it is known that all statement items in the variables (X1, X2, and Y) have a significance value of 0.000 <0.05, so that each variable is declared valid. Then in the reliability test, it is known that each variable has a Cronbach's Alpha value> 0.60, so that the variable is declared reliable. Furthermore, in the t-test, it is known that all variables (market orientation and networking) have positive values ​​and significance <0.05 so that they are stated to have a partial significant effect on purchasing decisions. Then in the F-test, the Sig. value for all variables together is 0.000 <0.05 and the Fcount value> Ftable, it can be concluded that the market orientation and networking variables simultaneously affect sales volume at Tandjaja Farm.